Prasugrel, a Platelet P2Y12 Receptor Antagonist, Improves Abnormal Gait in a Novel Murine Model of Thrombotic Hindlimb Ischemia - Kousaku Ohno; Atsuyuki Tomizawa; Makoto Mizuno; Joseph A. Jakubowski; Atsuhiro Sugidachi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundThe efficacy of P2Y12 inhibition for the prevention of cardiovascular events in patients with peripheral arterial disease (PAD) has been established. However, the therapeutic effects on ischemic limb complications are less clear. Accordingly, we aimed to develop a novel murine model of thrombotic hindlimb ischemia to reflect that found in patients with PAD exhibiting ischemic limb symptoms. We further investigated the effects of P2Y12 deficiency and P2Y12 inhibition by prasugrel in this model. Methods and ResultsThrombus formation induced by application of ferric chloride to the femoral artery resulted in a significant reduction in blood flow in the injured limb. In gait analysis using the CatWalk system, moderate difficulties in grounding and weight bearing of the ischemic limb, including reduction of maximum contact area and stance phase duration and increasing in swing phase duration in the ischemic limb, were observed in this model. Blood flow reduction and gait abnormalities gradually recovered over 21 days to levels present before arterial injury. Compared to wild‐type (WT) mice, significant increases in blood flow and improvement in gait were observed in P2Y12‐deficient mice. In addition, daily oral administration of prasugrel (3 mg/kg per day) to WT mice resulted in significant inhibition of blood flow reduction and gait abnormalities to levels found in P2Y12 deficient mice. ConclusionsAcute femoral artery thrombosis resulted in hindlimb ischemia and moderate gait abnormalities in mice. In addition, the present study suggests a possible role of P2Y12 in the complications with thrombotic limb ischemia.